Antioxidant potential of methanol Root extract of Mentha arvensis L. from Kashmir Region - M. Akbar Dara, Mubashir H. Masoodia, Adil F. Walia, Mudasir A. Mira, Nida S. Shapoob (Journal of Applied Pharmaceutical Science, 2014)
The study was carried out to evaluate the phytochemical constituents and antioxidant potential of methanolic root extract of Mentha arvensis L. from Kashmir region. The antioxidant activity of methanol extract of Mentha arvensis L. was evaluated by using 1, 1-diphenyl, 2-picrylhydrazyl (DPPH) scavenging, reducing power, metal chelating, nitrous oxide scavenging and hydrogen peroxide scavenging assays. The total phenolic content and total flavonoid content was found to be 9.12 and 32.14 mg/g respectively. The percentage inhibition values of DPPH scavenging for methanol extract were found to be 35.83%. The percentage inhibition values of Nitrous oxide scavenging for extract were found to be 39.11%, the percentage inhibition values of H2O2 scavenging for extract were found to be 21.72%, the percentage inhibition values of metal chelating activity of methanol extract at the concentration of 500 μg/ml was found to be 79.31% and that for standard ascorbic acid was found to be 96% at same concentration and the reducing power of extract was found to be 0.75 at concentration of 0.25mg/ml. The results indicate that the methanolic root extract of Mentha arvensis L. has good antioxidant potential and it can be regarded as promising candidates for natural plant sources of antioxidants with high.
Keywords: Mentha arvensis, DPPH, reducing power, nitrous oxide, metal chelating, H2O2.